Exploring the efficiency of platform economy: A prisma compliant systematic review of data envelopment analysis applications - Katerina Fotova Čiković; Damira Keček; Mirko Smoljić (UTMS Journal of Economics, 2022)
This paper reports on a systematic literature review of 14 empirical studies which address various aspects of platform economy with the application of the non-parametric DEA methodology. This review aimed to present the different aspects of efficiency evaluation of platform economy-based businesses with the applications of DEA. A secondary aim was to present recommendations or areas for future research in this area. A systematic search of the online Scopus scientific database has been conducted, with no restrictions to language, date of publication or study design. The methodology draws from the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The results of the 14 surveyed studies are presented in a narrative synthesis. Despite increasing academic and public interest in the platform economy, research on platform economy-based business has not been examined in a systematic study. Moreover, the applications of DEA methodology in this area of research have not been explored. This review examines the current state of knowledge about what platform economy is, the different aspects researched, the DEA models and extensions used and the future research potentials. The findings are discussed in detail. Moreover, specific literature gaps are identified, and suggestions and implications for further research are provided.
Keywords: C14; C69; L14; L19; L81; L82; 330; platform economy; DEA; data envelopment analysis; PRISMA; literature review